Deciphering supramolecular arrangements, micellization patterns, and antimicrobial potential of bacterial rhamnolipids under extreme treatments of temperature and electrolyte - Sikandar, Samia; Jamal, Asif; Mansoor, Afsheen; Bekhit, Mounir M.; Ghazanfar, Shakira; Ali, Muhammad Ishtiaq; Urynowicz, Michael; Huang, Zaixing (Frontiers in Microbiology, 2024)
The micellization properties of rhamnolipids (RLs) in extreme electrolyte concentrations and temperatures have gained considerable attention due to their broad industrial applications. In this study, the aggregation behavior, specifically the micellization pattern (CMC) of RLs produced from a newly isolated thermophilic strain of Pseudomonas aeruginosa from a harsh environment of an oil field, was investigated by a spectrophotometric method at various temperatures (293 K-393 K) and electrolyte concentrations (NaCl: 2%-20%). The result indicated that the CMC values (0.267-0.140 mMdm -3 ) were both electrolyte-and temperature-dependent exhibiting a U-shaped trend as temperature and NaCl concentration increased. Variations in NaCl concentration and temperature also affected the standard Gibbs free energy (ΔG o mic), enthalpy (ΔH o mic), and entropy (ΔS o mic) of micellization. The molecule also showed stability at a broad range of temperatures, pH, and NaCl concentrations. Thin-layer chromatography (TLC) and Fourier-transform infrared (FTIR) analysis confirmed the similarity in composition between the crude extract and the commercial RL with Rf values of 0.72 for mono-rhamnolipids and 0.28 for di-rhamnolipids. FTIR analysis confirmed the chemical nature particularly key aliphatic functional groups present in the fatty acid tail of RLs and the -COC-bond in the structure of the rhamnose moiety. Additionally, LC-ESI-QTOF analysis confirmed corresponding ionic fragments of mono-and di-rhamnolipids congeners. Furthermore, the antimicrobial potential was determined against different human pathogens in the absence and presence of NaCl by measuring zones of inhibition. The result revealed enhanced inhibitory effects against Gram-positive pathogens (S. aureus, S. epidermidis and L. monocytogene), with zones of inhibition of 26, 30, and 20 mm in the presence of NaCl.These findings underline the role of NaCl in the micellization of RL molecules and highlight their importance in environmental applications, pharmaceuticals, and various life science sectors.